The magic school bus on the ocean floor - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1992)
On a special field trip aboard the magic school bus, Ms. Frizzle's class learns about the ocean and the different creatures that live there.
Wilson's Children
Elem. School Library Collection
School Library Journal starred
3.9
K-3
Keywords: Marine animals -- Juvenile literature; Ocean bottom -- Juvenile literature; Ocean; Marine animals; Ocean; Marine animals